Medical Biophysics - CĂLINESCU, Octavian (Presa Universitară Clujeană, 2024)
This book was written for first year medical students, in particular, those studying medicine in English at the “Carol Davila” University of Medicine and Pharmacy Bucharest. However, even if you, the current reader, are not in that position, this book might still be for you if are interested in biophysics or the functioning of the human body in general.